2021
DOI: 10.3390/catal11010118
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Activity of Beta-Cyclodextrin-Gold Nanoparticles Network in Hydrogen Evolution Reaction

Abstract: The current climate crisis warrants investigation into alternative fuel sources. The hydrolysis reaction of an aqueous hydride precursor, and the subsequent production of hydrogen gas, prove to be a viable option. A network of beta-cyclodextrin capped gold nanoparticles (BCD-AuNP) was synthesized and subsequently characterized by Powder X-Ray Diffraction (P-XRD), Fourier Transform Infrared (FTIR), Transmission Electron Microscopy (TEM), and Ultraviolet-Visible Spectroscopy (UV-VIS) to confirm the presence of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…A catalyst that remains functionally inactive at temperatures of 40 • C or lower and activates at temperatures of 100 • C or higher is called a switchable catalyst. A wide range of technologies have been reported to realize these catalytic switching properties, including encapsulating the catalyst in compounds such as cyclodextrin [9][10][11][12][13][14][15][16]. For instance, Wang et al reported smart supramolecular nano-enzymes with temperature-driven switching properties have been successfully constructed by the selfassembly of supra-amphiphiles formed by the cyclodextrin-based host-guest chemistry [9].…”
Section: Introductionmentioning
confidence: 99%
“…A catalyst that remains functionally inactive at temperatures of 40 • C or lower and activates at temperatures of 100 • C or higher is called a switchable catalyst. A wide range of technologies have been reported to realize these catalytic switching properties, including encapsulating the catalyst in compounds such as cyclodextrin [9][10][11][12][13][14][15][16]. For instance, Wang et al reported smart supramolecular nano-enzymes with temperature-driven switching properties have been successfully constructed by the selfassembly of supra-amphiphiles formed by the cyclodextrin-based host-guest chemistry [9].…”
Section: Introductionmentioning
confidence: 99%
“…Beta-cyclodextrin’s unique shape as nanocup aids in its efficiency as a capping agent [ 10 ]. The deep hydrophobic internal cavity in the center of the molecule confines nanoparticles within its narrow walls which prevents agglomeration by restricting their ability to grow unchecked [ 10 ]. This effect results in isolated and uniform particles, which are more efficient catalysts due to their increased available surface area.…”
Section: Resultsmentioning
confidence: 99%
“…This has provided a great deal of positive change for numerous applications such as sensors, adsorbents, solar cells, and catalysis [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. The unique properties of nanomaterials are ultimately driving their application in many fields, and their dimensions allow them to replace conventional materials to provide smaller, more efficient technologies [ 8 , 9 , 10 ]. This allows typically costly materials, such as precious metals, to be applied in economical ways with more efficient means, ultimately stretching global reserves further.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations